High-contrast, reversible change of thermal conductivity in hexagonal nickel-iron sulfides. (15th April 2021) - Zhang, X.K.; Li, J.Y.; Lin, J.C.; Tong, P.; Wang, M.; Wang, X.L.; Tong, H.Y.; Zhang, Y.S.; Song, W.H.; Sun, Y.P.
Abstract: Materials showing abrupt change of thermal conductivity are strongly desired for rapidly developing thermal regulation applications. Here, we report a sharp change of thermal conductivity (Δ κ / κ 0 ) up to 200% within a temperature interval of 40 K in hexagonal sulfides Ni1- x Fe x S bonded with silver. Such Δ κ / κ 0 values exceed those reported in other thermal regulation materials, e.g., VO2 series (Δ κ / κ 0 <100%). The large jump of thermal conductivity roots from the dramatic modification of the electronic structure at the first-order phase transition. Moreover, the addition of silver overcomes the inherent brittleness of Ni1- x Fe x S and thus improves machinability and thermal cycling stability, which is beneficial to the practical applications. Our work presents a new promising material for thermal management applications. Graphical Abstract: Image, graphical abstract